Is there an impact of measurable residual disease as assessed by multiparameter flow cytometry on survival of AML patients treated in clinical practice? A population-based study. Issue 8 (3rd July 2021) - Rosso, Aldana; Juliusson, Gunnar; Lorenz, Fryderyk; Lehmann, Sören; Derolf, Åsa; Deneberg, Stefan; Jädersten, Martin; Antunovic, Petar; Cammenga, Jörg; Möllgård, Lars; Wennström, Lovisa; Ölander, Emma; et al.
Abstract: The Swedish national guidelines for treatment of acute myeloid leukemia (AML) recommend analysis of measurable residual disease (MRD) by multiparameter flow cytometry (MFC) in bone marrow in the routine clinical setting. The Swedish AML registry contains such MRD data in AML patients diagnosed 2011–2019. Of 327 patients with AML (non-APL) with MRD-results reported in complete remission after two courses of intensive chemotherapy 229 were MRD-negative (70%), as defined by <0.1% cells with leukemia-associated immunophenotype in the bone marrow. MRD-results were reported to clinicians in real time. Multivariate statistical analysis adjusted for known established risk factors did not indicate an association between MFC-MRD and overall survival (HR: 1.00 [95% CI 0.61, 1.63]) with a median follow-up of 2.7 years. Knowledge of the importance of MRD status by clinicians and individualized decisions could have ameliorated the effects of MRD as an independent prognostic factor of overall survival.